Inclusion of kenaf as bio-material component in sustainable manufacturing in Malaysian automotive industry - Amir Mustafa, Amira Mas Ayu (2019)
Increase in societal demand for sustainability has resulted in attention to sustainable manufacturing. Many manufacturers often focus on the economic component sustainability, neglecting the environmental and social aspects. Natural fiber reinforced polymer composites (NFC) provides a practical alternative to synthetic fiber reinforced composites largely in automotive and building product applications. At the laboratory scale, kenaf fibers reinforced polymer composites (KFC) has been proven that it is technically feasible to be developed as part of automotive bio-material components. The purpose of this study is to investigate whether such potential applications could meet the environmental and economic sustainability measurements. As illustration, the supply chain process of spare wheel cover production was used for this purpose. The first objective of the study describes the use of life cycle assessment (LCA) of utilizing kenaf fiber composites for spare wheel cover production. A cradle to gate assessment was performed based on the ISO 14040/14044 guidelines. The aims are to identify the major hotspots and most significant contributions to environmental pollution. The second objective of the study is to conduct an economic valuation of the consumer preferences from the Klang Valley area on using natural fiber composites in certain components of their car. The double bounded dichotomous- choice contingent valuation method (CVM) could be used for this purpose to solicit the interests of consumers to make extra payments towards reducing the impact to the environment. The third objective is to frame out a financial and economic feasibility assessment of using Kenaf fiber composites in the production of the spare wheel cover. The environmental cost and economic value estimates of the intangible environmental and economic impacts obtained from the previous objectives are incorporated into the cashflows to enable the computation of an economic cost-benefit analysis (CBA). Incorporating the three elements of the above study could shed light as to the environmental and economic sustainable development of Kenaf application into the automotive industry.